Comparison of Deep Sedation With General Anesthesia in Patients Undergoing Percutaneous Mitral Valve Repair. Issue 12 (2nd December 2017) - Patzelt, Johannes; Ulrich, Miriam; Magunia, Harry; Sauter, Reinhard; Droppa, Michal; Jorbenadze, Rezo; Becker, Annika S.; Walker, Tobias; von Bardeleben, Ralph Stephan; Grasshoff, Christian; Rosenberger, Peter; Gawaz, Meinrad; et al.
Abstract : Background: Percutaneous edge‐to‐edge mitral valve repair (PMVR) has become an established treatment option for mitral regurgitation in patients not eligible for surgical repair. Currently, most procedures are performed under general anesthesia (GA). An increasing number of centers, however, are performing the procedure under deep sedation (DS). Here, we compared patients undergoing PMVR with GA or DS. Methods and Results: A total of 271 consecutive patients underwent PMVR at our institution between May 2014 and December 2016. Seventy‐two procedures were performed under GA and 199 procedures under DS. We observed that in the DS group, doses of propofol (743±228 mg for GA versus 369±230 mg for DS, P <0.001) and norepinephrine (1.1±1.6 mg for GA versus 0.2±0.3 mg for DS, P <0.001) were significantly lower. Procedure time, fluoroscopy time, and dose area product were significantly higher in the GA group. There was no significant difference between GA and DS with respect to overall bleeding complications, postinterventional pneumonia (4% for GA versus 5% for DS), or C‐reactive protein levels (361±351 nmol/L for GA versus 278±239 nmol/L for DS). Significantly fewer patients with DS needed a postinterventional stay in the intensive care unit (96% for GA versus 19% for DS, P <0.001). Importantly, there was no significant difference between DS and GA regarding intrahospital or 6‐month mortality. Conclusions: DS for PMVR is safe and feasible. No disadvantages with respect to procedural outcome or complications in comparison to GA were observed. Applying DS may simplify the PMVR procedure.